Pengembangan LKPD Berbasis PBL Berbantuan PhET Simulation untuk Meningkatkan Hasil Belajar IPA pada Materi Getaran dan Gelombang di MTs Negeri 1 Bantul - Sumiasyih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to analyze the implementation of learning and improve student learning outcomes through the development of PBL-based LKPD assisted by PhET Simulation on vibration and wave materials. This study used the LKPD development design with two experiments. The results of this study provide data on the implementation of learning at the first and second meetings with a percentage of 100% with very good criteria. The results of students' responses to this learning obtained a score of 8.94 with a high category. The improvement in cognitive learning outcomes in vibrational materials with the Gain-score calculation at the first meeting was 0.35 increased to 0.56. At the second meeting the wave material entered the moderate category, with the interpretation of the effectiveness of N-Gain at a percentage of 56-75 categories quite effective. Improved learning on the affective aspect, the experimental results at the first meeting obtained an average of 75.0 rising to 86.3 at the second meeting. The results of the observation of student activities with an average score of 88.22 at the first meeting increased to 88.33 at the second meeting with excellent student activity criteria. PBL-Based LKPD Assisted PhET Simulation can be applied to students at the Tsanawiyah madrasah level.